Critical stages : the IATC Webjournal - International Association of Theatre Critics (International Association of Theatre Critics, 2009)
Critical Stages/Scènes critiques is available online to the reader without financial or technical barriers. It is a peer-reviewed journal fully committed to the Open Access Initiative. It offers a platform for debate and exploration of a wide range of theatre and performance art manifestations from all over the world. Our aim is to make our readers feel that Critical Stages/Scènes critiques is their "local" journal with a global reach.
Keywords: Theater : Periodicals; Performance art : Periodicals; Dramatic criticism : Periodicals; Théâtre : Périodiques; Critique dramatique : Périodiques; Dramatic criticism; Performance art; Theater